Observation of mode-coupling in few mode fiber bragg gratings - Lim, Kok Sing; Ali, M.M.; Loo, C.C.; Chong, W.Y.; Ahmad, Harith (2014)
Eight Bragg wavelengths are observed in the reflection spectra of a 4-mode optical fiber Bragg grating. The additional wavelengths are the results of coupling between two different transverse modes in the grating structure.